Propagação in vitro e ex vitro de louro-pardo (Cordia trichotoma (Vell.) Arrabida ex Steudel) - Heberle, Michele (2010)
Although the louro-pardo (Cordia trichotoma Vell.) is native forest specie with high timber potential, there are still scarce studies that approach the production of seedlings of this species by vegetative propagation. The objective of this work was to evaluate the vegetative propagation of the louro-pardo by the techniques of cuttings and micropropagation. It was tested the presence or absence of 8000 mg L-1 of indolbutiric acid (IBA) and two types of cuttings (basal and apical). At 40 days, the cuttings were evaluated for survival, rooting, the presence of callus and shoots, the number and length of shoots and the number of leaves. For the establishment of aseptic seedlings, seeds of louro-pardo were treated with 2% or 5% of sodium hypochlorite, for 0, 5, 10, 15 or 20 min. The seeds were inoculated in WPM basic culture medium. At 30 days, the percentages of disinfection, fungal contamination and / or bacteria and the average time of germination were evaluated. For multiplication, apical segments were inoculated in basic medium, plus 0; 0,25; 0,50 or 0,75 mg L-1 of 6-benzilaminopurin (BAP). At 45 days were evaluated the length, number of leaves and internodes of the shoots, the percentage of callus and the survival of the explants. In the multiplication, using microstumps kept in vitro, was tested whether or not the addition of 1,5 g L-1 of activated charcoal to the basic medium on the production of shoots. At 30 and 60 days, concerning to the first and second cuts of microstumps, were evaluated the number and length of shoots, number of leaves and internodes of the shoots, and the number of microcutting. Rooting in vitro microcuttings were maintained in basic medium plus 1,5 g L-1 of activated charcoal and IBA (1,5 or 2,0 mg L-1). At 45 days were evaluated the presence of roots and callus, the percentage of survival and sprouting. In cutting, were observed the formation of shoots on the cuttings, but they are not rooted. The cutting type and dose of IBA did not influence the rooting and survival. In micropropagation was found that the sterilization of seeds with 5% of sodium hypochlorite for 5 min. allowed the in vitro establishment of aseptic seedlings. The induction of shoots in the explants was not influenced by different doses of BAP. The presence of activated charcoal in the culture medium favored the formation and growth of shoots in microstumps. The use of 1,5 or 2,0 mg L-1 IBA did not promote the rooting of microshoots of louro-pardo.